2022
DOI: 10.1108/md-05-2022-0698
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: Over a half-century of management decision: a bibliometric overview

Abstract: A leading business science journal with the distinction of being the oldest and longest-running scholarly publication focused specifically on the area of management. (https://www. emeraldgrouppublishing.com/md.htm)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 47 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…Relying on authors' interaction and interpretation to delve into research streams and establish bridges across them, an interpretive approach was embraced to extract evidence of what makes OI viable in the public sector. Consistently with recent trends inspiring the scholarly debate in the field of management decisions (Caputo et al, 2022), our research addresses the following questions:…”
Section: Introductionmentioning
confidence: 80%
“…Relying on authors' interaction and interpretation to delve into research streams and establish bridges across them, an interpretive approach was embraced to extract evidence of what makes OI viable in the public sector. Consistently with recent trends inspiring the scholarly debate in the field of management decisions (Caputo et al, 2022), our research addresses the following questions:…”
Section: Introductionmentioning
confidence: 80%
“…This study chooses equity crowdfunding in China as the research context. It fills the research gap and addresses the call for more research encompassing China in management decision filed (Caputo et al. , 2022).…”
Section: Discussionmentioning
confidence: 97%
“…This study chooses equity crowdfunding in China as the research context. It fills the research gap and addresses the call for more research encompassing China in management decision filed (Caputo et al, 2022). We pioneer the research by applying social learning theory in crowdfunding and found that investors exhibit rational herding behavior.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of perceived and observed data can provide interesting insights into future research on corporate opinion leadership. Furthermore, as former studies examined individual characteristics of opinion leaders such as personality traits and competencies (Gnambs and Batinic, 2012), future research may investigate a company's features such as innovativeness or corporate social responsibility (Caputo et al. , 2022).…”
Section: Discussionmentioning
confidence: 99%